THE WAY TO LATGALIAN LITERATURE DURING THE 90s OF THE 20TH CENTURY - Kalniņa, Ieva (Via Latgalica, 2017)
During the 90s of the 20th century revival of Latgalian literature took place in the Republic of Latvia. It was a gradual process; in 2001 in “History of Latvian Literature" created by the Institute of Literature, Folklore and Art of the University of Latvia (ILFA) Ieva E. Kalniņa wrote about poetry of the 90s where she admitted that “it is already quite customary that poetry can be read in Latgalian written language”. Recent studies of Latvian literature in the 90s of the 20th century show that authors have different attitude towards Latgalian literature: Guntis Berelis has not included the revival of Latgalian literature in his list of the new phenomena of Latvian literature in his book “History of Latvian Literature”; among the ILFA researchers only Ieva E. Kalniņa mentions Oskars Seiksts, Anna Rancāne, Andris Vējāns, Osvalds Kravalis along with Vends and Livs among other phenomena of the 90s poetry; meanwhile in the review of prose and drama Latgalian literature is not mentioned at all. In 2007 Māris Salējs in his essay “Reflection on Latvian Literature 2000–2006” included Latgalian poets in the description of Latvian poetry, thus Valentīns Lukaševics and Juoņs Ryučāns together with Kārlis Vērdiņš and Marts Pujāts make up a characteristic trend. In the description of other genres Latgalian literature is not mentioned in this publication either. In this article the similarities and differences of Latvian and Latgalian literary revival process of the late 80s and the 90s of the 20th century are examined with special attention to the literary monthly magazine „Karogs” (Flag). The article deals with the development of literary process, cultural and historical methods are used to reach the aim of this paper – to find out what elements constitute the way to the establishment of Latgalian literature in Latvian cultural space and the importance of literary magazine „Karogs” in this process. There are several common trends of Latvian and Latgalian literary renewal in the 80s and 90s of the 20th century literary process: 1) return of repressed Latvian and Latgalian writers and their work to Latvian culture (such as Marta Skuja); 2) broad entry of exile literature into circulation for Latvian readership (Jānis Klīdzējs Marija Andžāne, etc.); 3) reprinted works, written during the 20s and 30s and unpublished in the Soviet time (Aleksandrs Adamāns); 4) in both traditions a number of exile periodicals begin to come out and some Latvian time periodicals are restored („Acta Latgalica”); 5) return of exile archives to Latvia („Latgaļu sāta”). Postmodern tendencies are observed not only in works of Aivars Ozoliņš, Jānis Vēvers or Gundega Repše, but also in creative work of O. Seiksts. Latgalian language and literature in Latvian cultural space has a special situation: there are important tasks to complete – to create a new alphabet, restore confidence in Latgalian literature in both traditions, the young and middle generation have to start writing in Latgalian tradition. Monthly magazine “Karogs” vividly reveals the new trends in Latgalian literature of the turn of the 80s and 90s, an important role is played by editor Andris Vējāns. It was „Karogs” which published one of the most influential texts of national awakening in Latgalian tradition – poem by O. Kravalis „Brōļ, pīmiņ!” (Brother, remember!). This publication is undeniably regarded as programmatic in Latvian and Latgalian literary traditions, declaring the return of Latgalian tradition and accepting the existence of both literatures. Among important publications in 1988 in the magazine about remembrance of Latgale cultural week, there was an article by Antons Stankēvičs „Atkusnī uzplaucis zieds” (A thaw flower) and Juris Pabērzs’ article „Skan joprojām” (It still sounds) where the role of the minister of culture Voldemārs Kalpiņš was emphasized. Poetry section published a poem of Antons Kūkojs „Atceroties Latgales kultūras nedēļu pirms 30 gadiem” (Remembering Latgale cultural week 30 years ago). The 1989 concept of magazine „Karogs” is obvious in publications of Latvian and Latgalian texts as a desire to respect the two literary traditions and present them to readers throughout Latvia. In 1990 and 2000 when the editor is Māra Zālīte, works of Roberts Mūks, A. Rancāne, J. Klīdzējs are published, some of them are in Latgalian, but mainly publications are in the Latvian literary language. There are two important articles in „Karogs”. Issue No.4, 1994 published Janīna Kursīte’s article „Latgaliešu literatūra – kas tu esi?” (Latgalian literature – who are you?), where the importance of dialects was emphasized and their ability to enrich the Latvian language, also this article pointed out the importance of periphery for the development of centre. Regarding recent Latgalian literature J. Kursīte’s assessment is blunt:”If one looks more carefully at what is published in the Latgalian literary language, one cannot overlook that artistically much of it is “rubbish”.” In 1997 was published Ilga Muižniece’s elegant review „Rūgtais pieradums – (ne dzīvot)” (Bitter habit – (not to live)) about O. Seiksts’ and V. Lukaševics’ novel „Valerjana dzeive i redzīni” (Valerjan’s life and opinions). The 90s mark two cultural traditions of Latgalian literature: 1) to some extent in the Latvian tradition Latgalian literature is viewed as an ethnographic tradition, which shows the possibilities of the Latvian language, diversity of traditions, complements Latvian literature with Latgalian vitality and charm, marks its catholic orientation, shows the natural beauty of Latgale; 2) Latgalian literature is considered an independent literature, writing in Latgalian is authors’ way of self-expression, it does not try to add anything to Latvian literary tradition, and it is based in Latgale and together with the Latvian literary tradition forms Latvian literature. Revival of Latgalian literature is one of the brightest features of culturally restored independent Latvia.